The Influence Of Product Credibility On Customer Loyalty: The Effect Of Perceived Value And Customer Satisfaction In Hangzhou - Liyun, Pan; Ali, Dhakir Abbas (Journal of Neonatal Surgery, 2025)
Because revenue is based on long-term client ties, client churn is a big problem in relational services. This includes industries like retail banking and telecoms. Retaining customers in this industry has traditionally revolved around ensuring their happiness and providing them with top-notch service. In an effort to lower the customer turnover rate of relational service, this study investigates the significant supplementary function of the brand. According to the researcher's information economics perspective, the brand's credibility is a key factor in the brand's potential engagement in this process. The study's findings shed light on the importance of the brand in maintaining long-term customer connections, the correlation between customer happiness and service quality—two popular CRM indicators—and more. Customers who were happy and loyal were less inclined to move brands, according to research. Customers of both retail banks and long-distance telephone companies were affected by this. The Researchers go over the study's theoretical and practical implications. This information is derived from a survey of Taiwanese mobile phone users. First things first: according to the study's findings, customers do not place a high value on tangibles or punctuality when evaluating service quality and value. Quality of the network, assurance, and dependability, however, do. Secondly, perceived value moderates, to a lesser extent, the association between total service quality and brand equity. Finally, there are a number of ways in which the overall quality of service mediates the connections between the value that customers perceive and the factors that contribute to that value. To conclude, brand equity is directly affected by empathy and network quality.